Study on the factors affecting the refractive index change of chalcogenide films induced by femtosecond laser. (December 2019) - Xiao, Chuanfu; Song, Baoan; Jin, Youliang; Zhang, Xue; Lin, Changgui; Zhang, Peiqing; Dai, Shixun
Highlights: The refractive index of the film decreases 0.02–0.08 after irradiation. The film after irradiation exhibits 2% photo-expansion. The refractive index change and photo-expansion remain a linear relationship. The photo-expansion is the main reason for the decrease of the refractive index. The refractive index decrease is related to a less connected glass network. Abstract: Femtosecond (fs) laser-induced functional microstructure in transparent chalcogenide film has potential application value in the field of novel infrared micro-nano photonic devices. Refractive index and thickness control of the film are crucial to manufacture infrared photonic devices. However, the changes of the refractive index and thickness induced by fs laser are too tiny to be characterized. In this condition, we designed and developed a method for studying the influencing factors of small refractive index changes induced by fs laser irradiation process. We obtained 64 different modified regions in chalcogenide film by using the laser direct writing technology. The transmission spectra of these fs laser-modified regions were recorded by use of micro-FTIR spectrometer. The refractive index and thickness of the transparent film before and after irradiation were calculated by an improved Swanepoel method. The dependence of the refractive index variation and the photo-expansion in the chalcogenide film on irradiation parameters (laser power and stage translational speed) was obtained quantitatively for the first time as far as our knowledge. The results show that the transparent chalcogenide film exhibits expansion and decreasing refractive index after fs laser irradiation. The transition threshold from non-thermal to thermal has been estimated for the Ge20 Sb15 Se65 film to be 15.6 GW/cm 2 . There is a linear relationship between refractive index change and photo-expansion around the threshold. Raman spectroscopy analysis of the modified area suggests that the change of refractive index and thickness may be due to the reduction in glass network connectivity of the Ge-based film induced by fs laser.